Age-Related Effects on the Spectrum of Cerebral Visual Impairment in Children With Cerebral Palsy - Galli, Jessica; Loi, Erika; Molinaro, Anna; Calza, Stefano; Franzoni, Alessandra; Micheletti, Serena; Rossi, Andrea; Semeraro, Francesco; Fazzi, Elisa; , CP Collaborative Group (Frontiers in Human Neuroscience, 2022)
Background: Cerebral Visual Impairment (CVI) is a very common finding in children affected by Cerebral Palsy (CP). In this paper we studied the characteristics of CVI of a large group of children with CP and CVI, describing their neurovisual profiles according to three different age subgroups (subgroup 1: infants 6 months-2 years; subgroup 2: pre-school age 3-5 years; subgroup 3: school age ≥ 6 years). Methods: we enrolled 180 subjects (104 males, mean age 66 ± 42.6 months; range 6-192 months) with CP and CVI for the study. We carried out a demographic and clinical data collection, neurological examination, developmental or cognitive assessment, and a video-recorded visual function assessment an evaluation of ophthalmological characteristics, oculomotor functions, and basic visual functions. In school-aged children, we also performed an evaluation of a their cognitive-visual profiles. Results: There were signs of CVI in all the three subgroups. Subgroup 1 (62 children) and subgroup 2 (50 children) were different for fixation (p=0.02), visual acuity (p=0.03) and contrast sensitivity (p<0.01), being more frequently impaired in younger children. Comparing subgroup 2 with subgroup 3 (68 children), the older children presented more frequently myopia (p=0.02) esotropia (p=0.02) and alteration in smooth pursuit (p=0.03) and saccades (p<0.01). Furthermore, fixation, smooth pursuit, visual acuity, contrast sensitivity and visual filed (p<0.01) were more frequently impaired in younger children (subgroup 1) compared to the older ones. Multiple correspondence analysis confirmed the different neurovisual profiles according to age: younger children with CP showed more signs of CVI compared to the older ones. 34 out of 68 children belonging to subgroup 3 underwent the cognitive visual evaluation; an impairment of cognitive visual skills was detected in 21 subjects. Conclusions: Younger children with CP showed more signs of CVI compared to the older ones, likely for the physiological maturation of visual system and mechanisms of neuroplasticity. In this direction, we suggest an early neurovisual evaluation to detect any weak visual functions